Diagnosis of the Digital Competence Gap between SMEs in Poland and the EU - Katarzyna Śledziewska; Renata Gabryelczyk (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
The purpose of this study is to point out the gap in the digital competence between SMEs in Poland and the European Union. For this evaluation the Eurostat database was used. A literature review in relation to organizational competence allowed the definition of digital literacy contained in the broadly defined ICT competence. Digital tools simplify and accelerate decision making processes throughout the management chain (EDI, ERP systems); allow the carrying out of more effective business analyses (cloud computing); facilitate transactions (e-commerce/e-invoicing), allow effective image and branding building (CRM systems, social media), facilitate penetration of new markets and reachingnew customers (e-commerce, CRM). The inference refers to the degree of digitization of SMEs in selected areas, and diagnosis of the digital skills gap in Polish small and medium-sized enterprises. The results of the analysis can be a starting point in building recommendations regarding the use of modern information and communication technologies by SMEs.
Keywords: O; 330; digital competence; digitizationof SMEs; Integration of Digital Technology